DIPG-40. Combined pharmacological and genetic screening to identify dependencies and combinations in ACVR1-mutant diffuse midline glioma. (3rd June 2022) - Rogers, Rebecca; Carvalho, Diana; Grabovska, Yura; Fernandez, Elisabet; Izquierdo, Elisa; Mackay, Alan; Jones, Chris
Abstract: Somatic mutations in ACVR1, which encodes the serine/threonine kinase ALK2, are found in 20-25% of DMG-H3K27 patients. Treatment of ACVR1-mutant patient-derived models with multiple chemotypes of ALK2 inhibitors (ALK2i) results in reduced cell viability in vitro and extended survival in orthotopic xenografts in vivo but, as single agents, these inhibitors were unable to achieve a complete anti-tumour response. Recently we reported that combinatorial treatment of ACVR1-mutant DIPG cells with vandetanib (RTK inhibitor) and everolimus (mTOR/ABC transporter inhibitor) was synergistic both in vitro and in vivo and was shown to be a feasible combination to trial clinically in this setting. To identify specific dependencies in ACVR1-mutant cells which may be translatable with novel synergistic drug combinations alongside ALK2i, we have implemented both candidate and unbiased drug and genetic screening approaches. Using a panel of patient-derived ACVR1-mutant and wild-type models, we identified synergy between multiple chemotypes of ALK2i (M4K2009/LDN-214117) and PI3K/mTOR (AZD8055/everolimus) and MEK inhibitors (trametinib), reflecting the common co-segregation of PIK3CA/PIK3R1 alterations in these tumours. Whole-genome CRISPR/Cas9 screening of ACVR1-mutant SU-DIPG-IV cells in combination with two ALK2i (M4K2009/LDN-193189), confirmed a specific MTOR genetic dependency, as well as for the protein phosphatase regulatory subunit PPP2R1A, known to play a role in MAPK pathway activation. Additional hits include the serine/threonine kinase PKMYT1, a negative regulator of the G2/M checkpoint via a functionally redundant phosphorylation of CDK1/CCNB1 alongside WEE1; confirmatory drug assays with the WEE1 inhibitor AZD1775 resulted in a synergistic interaction with ALK2i in ACVR1-mutant cells. Hits were integrated with DepMap using 'gene-effect' scores (Chronos) enabling filtering of common essential genes. Preliminary pathway enrichment analysis (MAGeCKFlute) identified ALK2i-specific vulnerabilities involving TGFB1/SMAD signalling and histone deacetylation. These data highlight functionally rational and novel combinatorial possibilities for children with ACVR1-mutant DMG, with systematic preclinical assessment required for prioritisation for the clinic.